The independence of Miss Mary Bennet - McCullough, Colleen, 1937-2015 (Simon & Schuster, 2009)
The best-selling author of The Thorn Birds presents a sequel to Pride and Prejudice that finds the willful third Bennet sister setting out in her late thirties in pursuit of adventure while her sisters worry about her at home.